Dywersyfikacja wiedzy o zarządzaniu kadrami - Kowalczyk, Stanisław; Owoc, Mieczysław L. (Knowledge diversification of human resource management, 2005)
Personal functions of firms are determined by several factors (for example growth of globalisation of economy or information revolution) observed in national enterprises environment. Enterprises need to possess knowledge of all crucial elements in the field of personnel functions and its ’environments in order to performance tasks fulfilling these functions. The paper is devoted to analyse of possibilities of aplaying intelligent systems supporting human resources management with stressing of knowledge diversification importance.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1064, s. 135-145